Tangled [videorecording (Blu-ray + DVD)] - Moore, Mandy, 1984-; Levi, Zachary, 1980-; Murphy, Donna; Garrett, Brad, 1960-; Perlman, Ron, 1950-; Tambor, Jeffrey, 1944-; Fogelman, Dan; Menken, Alan (Disney Blu-ray., 2019)
When the kingdom's most wanted bandit Flynn Rider hides in a mysterious tower, the last thing he expects to find is Rapunzel, a spirited teen with an unlikely superpower, 70 feet of magical golden hair! Together, the unlikely duo sets off on a fantastic journey filled with surprising heroes, laughter, and suspense.